Improving Network Lifetime in Secured Wireless Sensor Networks - Dr.B.Venkateshulu, Ch. Sudha Sravanthi (International Journal of Advanced Science and Technology, 2020)
Caser protocol helps in achieving lifetime and security in wireless sensor networks. In this paper, Caser protocol maintains equal energy levels in neighboring nodes by selecting next neighboring node based on highest energy level rather than selecting same node repeatedly as existing systems. Security is maintained by following two modes like random, non-random mode which helps in protecting source information from attackers. Simulation is performed in NS2. Results show random mode consuming less energy than non-random mode. As extension non-random mode is improved for maintaining both modes better in terms of energyKeywords: Energy Balance Control, Network Lifetime, Network Security,Wireless Sensor Network